Aluminium phthalocyanine-mediated photodynamic therapy induces ATM-related DNA damage response and apoptosis in human oesophageal cancer cells - Didamson, Onyisi Christiana; Chandran, Rahul; Abrahamse, Heidi (Frontiers in Oncology, 2024)
Introduction Photodynamic therapy (PDT) is a light-based technique used in the treatment of malignant and non-malignant tissue. Aluminium-phthalocyanine chloride tetra sulfonate (AlPcS4Cl)-mediated PDT has been well investigated on several cancer types, including oesophageal cancer. However, the effects of (AlPcS4Cl)-mediated PDT on DNA damage response and the mechanism of cell death in oesophageal cancer needs further investigation. Methods Here, we examined the in vitro effects of AlPcS4Cl-mediated PDT on cell cycle, DNA damage response, oxidative stress, and intrinsic apoptotic cell death pathway in HKESC-1 oesophageal cancer cells. The HKESC-1 cells were exposed to PDT using a semiconductor laser diode (673.2 nm, 5 J/cm2 fluency). Cell viability and cytotoxicity were determined by the ATP cell viability assay and the lactate dehydrogenase (LDH) release assay, respectively. Cell cycle and DNA damage response (DDR) analyses were conducted using the Muse™ cell cycle kit and the Muse® multi-color DNA damage kit, respectively. The mode of cell death was identified using the Annexin V-FITC/PI detection assay and Muse® Autophagy LC3 antibody-based kit. The intrinsic apoptotic pathway was investigated by measuring the cellular reactive oxygen species (ROS) levels, mitochondrial membrane potential (ΔΨm) function, cytochrome c levels and the activity of caspase 3/7 enzymes. Results The results show that AlPcS4Cl-based PDT reduced cell viability, induced cytotoxicity, cell cycle arrest at the G0/G1 phase, and DNA double-strand break (DSB) through the upregulation of the ataxia telangiectasia mutated (ATM), a DNA damage sensor. In addition, the findings showed that AlPcS4Cl-based PDT induced cell death via apoptosis, which is observed through increased ROS production, reduced ΔΨm, increased cytochrome c release, and activation of caspase 3/7 enzyme. Finally, no autophagy was observed in the AlPcS4Cl-mediated PDT-treated cells. Conclusion Our findings showed that apoptotic cell death is the main cell death mechanism triggered by AlPcS4Cl-mediated PDT in oesophageal cancer cells.